EMPLOYEE PERFORMANCE REVIEWED FROM LEADERSHIP STYLE, ORGANIZATIONAL CULTURE, WORK MOTIVATION AND WORK DISCIPLINE AT THE REGIONAL SECRETARIAT OF KLATEN REGENCY - Rimawati, Yeni; Sarsono, Sarsono; DPW, Ida Aryati (STIE Pelita Nusantara Semarang, 2025)
The study was conducted to determine the effect of leadership style, organizational culture, work discipline and work motivation on the performance of ASN of the Klaten Regency Regional Secretariat. This type of research is quantitative research. This research was conducted at the Klaten Regency Regional Secretariat and the research time was carried out from March to December 2024. This research was conducted on 80 employees at the Klaten Regency Regional Secretariat. The sampling technique used in this study was the census technique so that the sample numbered 80 people. The data in this study were processed using multiple linear regression analysis tools with the help of SPSS software. Based on the results of hypothesis testing and the discussion that has been carried out, it can be concluded as follows: Leadership style, organizational culture, work discipline, work motivation have a positive and significant effect on the performance of employees of the Klaten Regency Regional Secretariat. This means that the variables of leadership style, organizational culture, work discipline and work motivation contribute to ASN performance by 43.4% while the remaining 56.6% is explained by other variables.